PENGARUH RASIO LIKUIDITAS, RASIO AKTIVITAS, DAN RASIO PROFITABILITAS TERHADAP PRICE EARNING RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syafruddin Syafruddin (Universitas Riau Kepulauan, 2015)
In fundamental analysis, Price Earning Ratio is often used because it is easy to understood by investors or prospective investors as a measure to determine how the market value or price of a company. Financial ratios that used is liquidity ratio, activity ratio, and profitability ratio. The aims of this study is to determine the influence of liquidity ratio, activity ratio, and profitability ratio to Price Earing Ratio in manufacturing companies listed on the Indonesia Stock Exchange in 2010-2012. This study using a quantitative approach. Population in this research is all the manufacturing company listed in Indonesia stock exchange from 2010 until 2012. This samples are taken by using purposive random sampling. Number of samples are 12 manufacturing company listed on Indonesia stock exchange from 2010 until 2012. Variables examined included current ratio (CR), inventory turnover (INTO) and return on equity (ROE) as an independent variables, while the dependent variable is price earning ratio (PER). From the result shows that the liquidity ratio, and profitability ratio has a significant effects on price earning ratio manufacturing company shares. However activity ratio take effect on price earning ratio (PER) manufacturing company shares but not significantly. This research can be used as a reference for investors to predicting the company’s stock price in the future and in making decesions to invest.